Magkukuwento na si Lola: Ang Mga Kuwento ni Lola Basyang sa Libro, Teatro, Telebisyon, at Radyo - Bellen, Christine S. (Plaridel Journal of Communication, Media, and Society; Vol 6 No 1 (2009): Media and Folklore, 2011)
This paper analyzes how the popular stories of Severino Reyes have been translated into various forms of media. After Gilda Cordero-Fernando translated the story into English in 1997 for Tahanan Books, Lola Basyang stories became even more a part of children's literature. On the other hand, the publication of Lola Basyang picture books in 2004-2005 and 2007 paved the way for the stories to be adapted for dance, theater, television, and radio. Each of these media required different ways of adapting the classic stories.